Natural wetland in China - Xubin Pan; Jingyi Zhang; Zhongkui Luo; Limi Mao; Hongmei Jin; Liping Guo; Xiaoli Bi; Yuping Zhao (African Journal of Environmental Economics and Management, 2019)
As it is known to all, wetland is one of the most crucial ecosystems in the world, with large varieties in China. How to protect wetland in China has become a more serious problem and five typical wetlands were selected in the article to illustrate the condition. Through the comparison between the past and present of wetland, attention should be paid in adjusting the human behavior and the ways of producing and living.